Associations between seminal plasma triclosan and low sperm quality: A case-control study. (April 2023) - Guo, Yinsheng; Ma, Yue; Zhong, Weiqiang; Zhou, Lixiao; Wan, Yanjian; Zhu, Huiping; Zhang, Rong
Highlights: Seminal plasma TCS concentration were quantitatively tested using UPLC-MS/MS. TCS exposure status of 100 low sperm quality men and 100 control men were assessed. Seminal plasma TCS were significantly associated with risk of low sperm quality. Abstract: Objective: Triclosan (TCS), a novel endocrine disrupter, has induced widespread human exposure due to its widespread use in personal care products. Environmental TCS exposure was suggested to be associated with human semen quality. However, little is known about seminal plasma TCS concentration and the risk of low sperm quality. This case-control study is established to examine the relationship between seminal plasma TCS and the risk of low sperm quality. Study design: One hundred men with low sperm quality as cases and one hundred normal men as controls were recruited a fertility clinic in Shijiazhuang, China, during 2018–2019. Seminal plasma TCS concentration was determined using an ultrahigh-performance liquid chromatography-tandem mass spectrometer (UPLC–MS/MS). Sperm concentration, sperm count, sperm motility and sperm progressive motility were evaluated according to World Health Organization (WHO) guidelines to assess the sperm quality. We used the Mann–Whitney rank–sum test and Kruskal–Wallis test to assess the differences of seminal plasma TCS concentration between the cases and the controls. In addition, logistic regression analysis was used to estimate the associations between seminal plasma TCS concentrations and low sperm quality risk adjusting for age, body mass index (BMI), abstinence time, smoking, and drinking Results and conclusions: The level of seminal plasma TCS was observed slightly but not significantly higher in the case group than the control group. We also observed significant association between seminal plasma TCS concentrations and semen parameters in both control and case groups. Moreover, the seminal plasma TCS levels at the fourth quartile were found to be more likely to exhibit low sperm quality risk with increased adjusted odds ratios of 2.36 (95% confidence interval 1.03–5.39) compared to the first quartile. Our results reveal that seminal plasma TCS concentration was positively associated with low sperm quality risk.